Long-year follow-up of acute myocardial infarction with preserved initial LVEF: prognostic impact of progressively reduced LVEF. (25th November 2020) - Yoshioka, G; Watanabe, N; Shibata, Y; Node, K
Abstract: Background: Severely reduced left ventricular ejection fraction (LVEF ≤35%) is commonly seen in approximately 5% of the myocardial infarction (MI) survivors in its acute-phase, which is recognized as a risk factor of post-MI cardiac death. However, clinical incidence and risk factor of the progressively reduced LVEF in the chronic-phase after MI has not been clarified. Purpose: To evaluate clinical incidence and risk factor of the progressively reduced LVEF in the chronic-phase after MI by serial echocardiography. Method: We evaluated 1144 consecutive patients with acute MI with preserved LVEF (≥50%) in acute-phase. Primary outcome was severely reduced LVEF (<35%) in the chronic-pahse. We analyzed the predictive factor using multivariate analysis. Result: During follow-up (median:1097 days), severely reduced LVEF newly developed in 8.6% of AMI survivors. Kaplan-meier curve is shown in the Figure. Multivariate analysis showed that men, eGFR <30, AMI of LAD and absence of renin-angiotensin system blocking drugs was an independent predictor of severely reduced LVEF. Conclusions: Progressively reduced LVEF during chronic-phase occurred 8.6% in acute MI survivors with preserved initial LVEF. Especially patients with these risk factors, careful long-term follow-up after MI should be needed to identify possible candidate for the implantable cardioverter-defibrillator. Funding Acknowledgement: Type of funding source: None